Cytomegalovirus colitis in inflammatory bowel disease and after haematopoietic stem cell transplantation: diagnostic accuracy, predictors, risk factors and disease outcome. Issue 1 (27th February 2019) - Mavropoulou, Eirini; Ternes, Kristin; Mechie, Nicolae-Catalin; Bremer, Sebastian Christopher Benjamin; Kunsch, Steffen; Ellenrieder, Volker; Neesse, Albrecht; Amanzada, Ahmad
Abstract : Background: Concurrent cytomegalovirus (CMV) colitis in inflammatory bowel disease (IBD) and after haematopoietic stem cell transplantation (HSCT) is an important clinical entity associated with high rates of morbidity and mortality. Methods: A retrospective study of 47 patients with IBD and 61 HSCT patients was performed regarding the evaluation of diagnostic accuracy of applied methods, predictors, risk factors for CMV disease manifestation, the proportion of patients with antiviral treatment and disease outcome. Results: The sensitivity of quantitative PCR (qPCR) with a cut-off value of >250 copies/mg for CMV colitis in patients with IBD and HSCT patients was 79% and 92%, respectively. Predictors for CMV colitis in the IBD cohort were anaemia and the presence of endoscopic ulcers. Glucocorticoids, calcineurin inhibitors and >2 concurrent lines of treatment with immunosuppressive drugs could be identified as risk factors for CMV colitis in the IBD cohort with an OR of 7.1 (95% CI 1.7 to 29.9), 21.3 (95% CI 2.4 to 188.7) and 13.4 (95% CI 3.2 to 56.1), respectively. Predictors and risk factors for CMV gastroenteritis in the HSCT cohort was the presence of endoscopic ulcers (OR 18.6, 95% CI 3.3 to 103.7) and >2 concurrent lines of treatment with immunosuppressive drugs. Antiviral therapy was administered in 70% of patients with IBD and 77% of HSCT patients with CMV disease. 71% of antiviral-treated patients with IBD showed an improvement of their disease activity and 14% underwent colectomy. The mortality rate of HSCT patients was 21% irrespective of their CMV status. Conclusions: In addition to the implementation of histological methods, qPCR may be performed in patients with suspected high-risk IBD and HSCT patients for CMV colitis. Independent validations of these results in further prospective studies are needed.